PENERAPAN METODE PEMBELAJARAN PAAIKES UNTUK MENINGKATKAN ANTUSIASME ANAK SEKOLAH MINGGU DALAM BERIBADAH ONLINE DI GBI PAPUA RESTORATION FOR CHRIST - Yohanes Charly Panjaitan; Ferdinand Edu; Ivonne Sandra Sumual (Jurnal PKM Setiadharma, 2021)
During the Covid-19 pandemic, Sunday School Teachers are required to be able to carry out Sunday school worship properly with the essence and the right way. This is so that children do not experience boredom and can understand the material presented correctly and experience growth in faith according to their age. Therefore, the team carried out Community Service at GBI Papua Restoration For Christ by applying the PAAIKES teaching method to Sunday school children. The implementation method is carried out by teaching and mentoring. The results of PkM stated that the response was enthusiastic and enthusiastic from Sunday School children when worshiping and listening to God's word. Enthusiastic Sunday School children can be owned by the church if they apply the right teaching methods and give full attention such as providing the right mentoring and direction.